Engendering Public Policy A Report on the work of the Working Group of Feminist Economists during the Preparation of Eleventh Five Year Plan 2007-2013 - Planning Commission (Planning Commission Government of India, 2010)
The Working Group of Feminist Economists (WGFE) report on India’s Eleventh Five-Year Plan (2007–2012) represents a transformative effort to mainstream gender into national development planning. By recognizing women as economic agents rather than mere beneficiaries, the report advocates policies that enhance access to land, credit, and technology, particularly in agriculture and informal sectors. It emphasizes labor rights, social security, and skill development to strengthen women’s participation in the workforce. Recommendations also address health, education, financial inclusion, food security, and rural infrastructure, ensuring that development interventions are gender-sensitive. The WGFE framework provides a comprehensive blueprint for integrating gender equity into public policy, fostering inclusive growth and socio-economic empowerment across India.
Planning Commission Government of India May 2010
Keywords: Gender Inclusion; Women’s Empowerment; Agricultural Development; Economic Participation; Land Access; Employment Rights; Informal Sector; Health And Education; Financial Inclusion; Food Security; Infrastructure Development; Policy Reform